Biodiversity and Host–Parasite (Co)Extinction - van Dijk, Jeroen; de Baets, Kenneth (The Evolution and Fossil Record of Parasitism, 2021)
Parasitism is one of the most common modes of life, and yet it is often disregarded or ignored in nature conservation. We are at the brink of the sixth mass extinction and in order to assess the extinction risk of both parasites and their hosts, we first need to fully understand the role and function of parasites in ecosystems. Parasites might play an active role in their host’s extinction, and coextinction has been postulated to be the most common mode of extinction. However, parasites may be able to survive their host’s extinction through host switching, perhaps to a more abundant host, for example. The dilution effect has been described as an important natural defense mechanism for the host: higher biodiversity is associated with lower infection risk. Discussed here is the importance of biodiversity and host–parasite associations and (co)extinction, and the role the fossil record has in filling the knowledge gap regarding deep-time host–parasite interactions.
Keywords: Biodiversity; Co-extinction; Dilution effect; Host–parasite associations; Fossil record; Host switching